Kearifan lokal Bali untuk pelestarian alam: Kajian wacana kartun-kartun majalah “Bog-Bog” - I Wayan Swandi (Universitas Udayana, 2017)
An aggressive logging becomes a chronic problem in Indonesia. There is an inappropriate paradigm in the understanding and treating of the environment, especially trees and forests. This article examines the discourse of nature conservation based on Balinese local wisdom as presented in visual cartoons of Bog-Bog magazine (No 10, Vol 10, 2012) which theme is tree. Information data taken from cartoon Bog-Bog magazine No. 10, analyzed by the theory of semiotics and supported by the theory of visual design elements. The pictures from the Bog-Bog cartoon show the artistic, critical and humorous efforts of the Bog-Bog cartoonists in constructing Balinese local discourse based on customs, belief, and Hindu religion in an important message of preserving the forest in particular and nature in general. Analysis shown that Bali has a number of local wisdom such as the sacred trust system of tree as one of the ecological messages for forest preservation. An example is the concept of palemahan in the Hindu philosophy of Tri Hita Karana which is important for the harmony of human relationship with nature as a source of prosperity. Bog-Bog cartoon successfully convey the nature conservation discourse based on Balinese local wisdom with the construction of humor, critical, and parody discourse.